Proyeksi Jumlah Pergerakan Dalam Menentukan Kapasitas Dan Jumlah Armada Perintis Kabupaten Maluku Barat Daya - Johannes, Standy; Anwar, M. Ruslin; Kurniawan, Edd Basuki (Jurnal Tata Kota dan Daerah, 2012)
The splitting of Southwest Maluku District from the central district has been encouraging the increase of marine transport services demand. The condition of the region consisted of islands whose main access is by the sea and the low level of economic are the reasons why people prefer cheap rates rather than security and comfort in traveling. This can be seen in pioneering fleet cruise route (KM. Sabuk Nusantara 31) with a capacity of 400 passengers and 50 tons of goods covering 3.096 mile distance by 10 harbors on West Southeast Maluku route and 12 harbors on Southwest Maluku. Therefore, based on previously describred condition, the aim of this research was to investigate the loading condition by comparing existing supply and supply demand according to the existing movement data projected using trend projection method by liniar trend equation and forecasting accuracy assessment by squared error average value (MAPE). Consequently, this would lead to the finding of movement value in the next 10 year used to determine the type, number and capacity of the appropriate fleet. As a result of this study, fleet services condition of KM. Sabuk Nusantara 31 was not optimal based on capacity and range of services so that it required 1 additional pioneering fleet, 2000 type with the capacity of 2000 passengers, operated specifically to serve B route (Southwest Maluku District).Keywords : Forecast, Movement, Capacity, Southwest Maluku.